2014
DOI: 10.1117/1.oe.53.8.087109
|View full text |Cite
|
Sign up to set email alerts
|

Off-axis sputter deposition of ZnO films on c-sapphire substrates by utilizing nitrogen-mediated crystallization method

Abstract: Abstract. High-quality epitaxial ZnO films on c-plane sapphire substrates have been obtained by utilizing an offaxis sputtering configuration together with buffer layers prepared via nitrogen-mediated crystallization (NMC). The role of NMC buffer layers is to provide high density of nucleation site and, thus, to reduce the strain energy caused by the large lattice mismatch (18%) between ZnO and sapphire. The NMC buffer layers allow two-dimensional growth of subsequently grown ZnO films, being particularly enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…b, two peaks spaced by 180° were observed for both ZnO and sapphire, since the crystal lattices of m‐plane ZnO and m‐plane sapphire are both rectangular with two‐fold symmetry. The c ‐axes of ZnO and that of sapphire perpendicularly crossed each other on the sapphire substrate, namely ZnO [0001] || sapphire and ZnO || sapphire [0001]. In this φ scan measurement, the ZnO (10–11) and sapphire (11–20) planes were used as the monitoring planes, where Bragg conditions were set to be satisfied.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…b, two peaks spaced by 180° were observed for both ZnO and sapphire, since the crystal lattices of m‐plane ZnO and m‐plane sapphire are both rectangular with two‐fold symmetry. The c ‐axes of ZnO and that of sapphire perpendicularly crossed each other on the sapphire substrate, namely ZnO [0001] || sapphire and ZnO || sapphire [0001]. In this φ scan measurement, the ZnO (10–11) and sapphire (11–20) planes were used as the monitoring planes, where Bragg conditions were set to be satisfied.…”
Section: Resultsmentioning
confidence: 99%
“…and , it was shown that the thickness and crystallographic properties were homogeneous across the substrate, and that the ZnO film was epitaxially grown on the sapphire substrate . In the direction lateral to the sapphire substrate, four small rectangular ZnO lattices are formed on one large sapphire rectangular lattice in the sapphire [0001] direction, indicating domain‐matching epitaxy , where the lattice mismatch in the ZnO [0001] direction is 9.7%, and that in the ZnO direction is 0.1%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because of the low crystallization temperature of ZnO, it is difficult to obtain amorphous like layers by just lowering the deposition temperature. Recently, we have developed a new type of buffer layers fabricated by "nitrogen mediated crystallization (NMC) method", where nucleation and crystal growth is controlled by not lowering deposition temperature, but introducing impurity atoms that inhibit crystal growth [10][11][12][13]. By utilizing the buffer layers fabricated by NMC method (NMC-ZnO buffer layers), we have succeeded in fabrication of atomically-flat ZnO films on lattice mismatched sapphire substrates.…”
Section: Introductionmentioning
confidence: 98%